2019
DOI: 10.1093/ejcts/ezz131
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of perioperative outcome and long-term survival rate of thoracic endovascular aortic repair in uncomplicated type B dissection: single-centre experience with 751 patients

Abstract: OBJECTIVES To study the perioperative outcomes and long-term survival rates in patients undergoing thoracic endovascular aortic repair (TEVAR) for uncomplicated type B dissection. METHODS A total of 751 patients with uncomplicated type B dissection who underwent TEVAR at our centre between May 2001 and December 2013 were retrospectively reviewed. The mean age of all patients (619 males and 132 females) was 52.8 ± 10.9 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 22 publications
1
31
0
1
Order By: Relevance
“…In the present study, there was no difference in survival rates among the four types of lesions, as well as no difference in survival rates was found between the two kinds of bypass. In our center, the 5 and 10‐year survival rates for uncomplicated Type B dissection were 96.5% and 83.0%, respectively 24 . The median age of the hybrid group was older than that of the uncomplicated Type B dissection group, which may have caused this substantial difference between the survival rates.…”
Section: Discussionmentioning
confidence: 83%
“…In the present study, there was no difference in survival rates among the four types of lesions, as well as no difference in survival rates was found between the two kinds of bypass. In our center, the 5 and 10‐year survival rates for uncomplicated Type B dissection were 96.5% and 83.0%, respectively 24 . The median age of the hybrid group was older than that of the uncomplicated Type B dissection group, which may have caused this substantial difference between the survival rates.…”
Section: Discussionmentioning
confidence: 83%
“…Rupture and RTAD were the most commonly reported causes of aortic-related death in patients who underwent TEVAR for unTBAD. Rupture is associated with high mortality at the indexed event [21]. Other observational studies reported the incidence of aortic rupture to be 2.5%-5% [12,14,20].…”
Section: Aorta-related Mortality and Rupturementioning
confidence: 99%
“…Type II endoleak describes a backward flow from a single (IIa) or multiple (IIb) side branches as the intercostal or lumbar arteries into the false lumen [24,25]. Type I and Type II endoleaks are the most commonly observed endoleaks during later follow-up after TEVAR in un-TBAD [8,12,21,26]. Some endoleaks such as type Ia and Ib can eventually resolve on their own without any need for re-intervention [12,27].…”
Section: Late Endoleaksmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the strategy of stenting should be based on the pathologies and prognoses of individuals. In our center, for dissection involving the distal arch, we performed two-stent implantation with tapered stents to avoid endoleak ( 27 ). Notably, late reintervention may be unavoidable for degenerative aortic lesions.…”
Section: Commentmentioning
confidence: 99%